REALITY AND OUTLOOK OF CONTRACTUAL RELATIONSHIPS ON THE WHOLESALE ELECTRIC POWER MARKET IN UKRAINE - Sambur S.B.; Tihonchuk I.V. (Problems of the Regional Energetics)
There is analyzed mutual relationship between electricity seller of Ukraine (State Enterprise “Energorinok”) and the states of CIS and UCTE.